Target capital structure and speed of adjustment: a dynamic evidence from Shariah approved firms in Malaysia - Ramli, Nurshamimitul Ezza; Haron, Razali (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM), 2017)
The purpose of this paper is to identify the target capital structure and the speed of adjustment of Shariah approved firms listed on the Bursa Malaysia. The paper also examines the influence of firm, industry and macroeconomic determinants affecting the target capital structure. Shariah approved firms which consistently maintain their Shariah status as per the Securities Commission (SC) of Malaysia requirement, from year 2000 to 2014 are chosen as the sample of analysis. The paper employs a dynamic panel data technique specifically the Generalized Method of Moments (GMM) that is robust to the heterogeneity and endogeneity issue. The study found the existence of target capital structure of Shariah approved firms in Malaysia and in terms of speed of adjustment, Shariah approved firms are under-adjusted. Several factors seemed to have significant impact on the target capital structure ranging from the firm, industry and macroeconomic determinants. The study contributes largely in the sampling selection that focuses only on the Shariah approved firms which consistently maintain their Shariah status from the year 2000 to 2014.